The Boy With the Glass Flute - Rickson, Daphne (Voices: A World Forum for Music Therapy, 2003)
This study describes music therapy sessions over 21 months with a preadolescent boy who had several diagnoses including Atypical Asperger Syndrome, Attention Deficit Hyperactivity Disorder (ADHD), Reading Disability, and "probable" Conduct Disorder (CD). He had also been physically abused. John's initial rejection of music led me, as clinician, to question the appropriateness of a music therapy programme for him, the philosophical underpinnings of the work, and my skills as a clinician. However, by maintaining the humanistic existential framework that was familiar to me, and employing aspects of Paraverbal therapy, I was able to develop a relationship of trust with John and to facilitate his involvement in creative activities. Following an extremely tentative beginning he was able to communicate his love and fascination for music by creating the fantasy of owning a "glass flute", a symbolic object of beauty that can be enjoyed, but which was delicate and fragile. As his self awareness and identity became more established the image of the glass flute was replaced by the reality of recorder playing and he developed a new confidence in the mastery of music which allowed him to successfully perform for his peers and the general public.